A morphometric study of variation in dens of second cervical vertebrae: corona dentis and its clinical implication - Hiwarkar, Monali; Sharma, Shalika; Krishna, Prasad Anjali; Agarwal, Jolly; Singh, Harsimran Jit; Ramkumar, M. (International Journal of Research in Medical Sciences, 2025)
Background: Type-II odontoid fractures are often managed by anterior screw fixation, a technique that requires precise morphometric knowledge of the dens. The corona dentis, a bony spur at the odontoid apex, may artificially elongate measurements, leading to potential surgical complications if unrecognized. Methods: Thirty dry human C2 vertebrae were studied using a digital vernier caliper. Morphometric parameters of the dens and vertebral body were recorded, including height, anteroposterior (AP) and mediolateral (ML) diameters, and dimensions of the corona dentis. Non-metric features such as dens tip shape, orientation, and transverse ligament groove morphology were assessed independently by two observers. Measurements were repeated to minimize intra-observer variability. Results: Corona dentis was observed in 8 of 30 specimens (26.7%). The mean height of the dens without corona was 15.35±1.84 mm anteriorly and 15.65±1.70 mm posteriorly, whereas combined heights with corona averaged 18.95 mm and 19.25 mm, respectively. The corona itself measured 3.60±0.79 mm in height and 9.80±0.99 mm in width. The dens averaged 10.1±0.91 mm (AP) and 9.8±0.99 mm (ML). Non-metric analysis showed tapering tips in 40%, retroverted axes in 56.7%, and transverse-type ligament grooves in 60% of specimens. Conclusions: The corona dentis is a relatively common anatomical variation that significantly increases apparent dens height. Failure to recognize this structure may result in overestimation of screw length during anterior odontoid fixation. Preoperative CT evaluation and careful apex identification are essential for safe surgical planning.